International variance in the treatment of developmental dysplasia of the hip. (October 2014) - Feeley, I. H.; Green, C. J.; Rowan, F. E.; Moore, D. P.
Introduction: Developmental dysplasia of the hip (DDH) is the most common congenital musculoskeletal abnormality. Recourse to definitive surgical treatment is not typically taken until over the age of 18–24 months. International consensus regarding age at surgery, degree of dysplasia requiring surgery and type of osteotomy is not available in the literature. Study aims: To determine variation in timing and type of osteotomy for persistent DDH across the world. Methodology: Senior authors of recent publications pertaining to hip dysplasia were sampled. Participants' practice relating to age and radiological indications for surgery were determined. Results: Thirty-two surgeons responded from five different geographical regions. No inter-regional consensus was established regarding investigations to determine the need for osteotomy, preferred osteotomy type or ideal age at which to perform an osteotomy. Conclusion: International agreement regarding the surgical management of DDH does not exist. This common congenital condition warrants development of a treatment algorithm.